19 The mechanism of supply-demand imbalance and clinical outcomes in patients with type 2 myocardial infarction. (17th July 2020) - Bularga, Anda; Anand, Atul; Strachan, Fiona E; Lee, Ken K; Stewart, Stacey; Ferry, Amy V; Marshall, Lucy; McAllister, David; Shah, Anoop SV; Newby, David E; Mills, Nicholas L; Chapman, Andrew R
Abstract : Background: Type 2 myocardial infarction is common and associated with substantial risk of adverse clinical outcomes, worse than type 1 myocardial infarction, with as few as 30% of patients still alive at five years. However, this broad diagnostic term encompasses multiple mechanisms of supply-demand imbalance, which may be associated with different risks of adverse outcomes. Purpose: We aimed to assess the prevalence and clinical outcomes of different mechanisms of supply-demand imbalance related to survival in the High-STEACS (High-Sensitivity Troponin in the Evaluation of patients with Acute Coronary Syndrome) randomised controlled trial. Methods: The High-STEACS trial was a stepped wedge cluster randomised controlled trial in ten hospitals across Scotland, including 48, 282 consecutive patients with suspected acute coronary syndrome. The diagnosis was adjudicated according to the Fourth Universal Definition of Myocardial Infarction. In patients with type 2 myocardial infarction, we prospectively adjudicated the cause for supply demand imbalance. Linkage of electronic healthcare records was used to track investigation, treatments and clinical outcomes. We used the Kaplan-Meier method, the log rank test and cox regression models adjusted for age, sex, renal function and co-morbidities to evaluate the risk of future all-cause mortality between categories. Results: We identified 1, 121 patients with type 2 myocardial infarction (age 74¬ ± 14, 55% female). At one year, death from any cause occurred in 23% (258/1, 121) of patients. The most common reason for supply-demand imbalance was tachyarrhythmia in 55% (616/1, 121), followed by hypoxaemia in 20% (219/1, 121) of patients. Tachyarrhythmia was associated with reduced future risk of all-cause mortality (adjusted HR 0.69, 95%CI 0.43-1.09), similar to those with type 1 myocardial infarction. Comparatively, patients with hypoxaemia appeared at highest risk (adjusted HR 1.75, 95%CI 1.09-2.80). Conclusion: The mechanism of myocardial oxygen supply-demand imbalance is associated with future prognosis, and should be considered when risk stratifying patients with type 2 myocardial infarction. Conflict of Interest: No conflict of interest